Constative experimental study of values dynamics of the competence of personal, social development and learning to learn of primary school students - BICULESCU, Florina – Teodora (Acta et Commentationes, Sciences of Education, 2023)
The article contains experimental research at the acknowledgement stage aimed at evaluating the values of the competence of personal, social development and learning to learn in terms of axiological reference of students, by which we consider a system of desirable values, suitable to be formed in primary education. The pedagogical experiment was organized in grades 1-4, during 2018-2022 on a sample of 68 students from primary education. The experimental approach allowed the detection of the following problems that become impediments in the process of forming the values of the competence of personal, social development and learning to learn: difficulties in expressing empathy, respect for classmates and friendship, inconsistencies in affirmation by assuming responsibility, assertive communication, innovative spirit and autonomy in the school group, which demonstrates the need to design axiological education, at the level of functional strategies for the formation of the axiological referential that represents the competence of personal, social development and learning to learn of primary education students.